Chiari Type I Malformations in Patients with Dizziness. (2nd September 2014) - Mostovych, Nadia K.; Willcox, Thomas O.; Artz, Gregory J.
Abstract : Objectives: (1) Investigate the association between magnetic resonance imaging (MRI) findings of Chiari Type I malformation and symptoms of dizziness in patients presenting to a neurotology clinic. (2) Recommend indications for intervention for Chiari Type I malformation in patients presenting with dizziness. Methods: A retrospective chart review was conducted for 16 patients presenting to our neurotology clinic between 2002 and 2009 found to have Chiari Type I malformation on MRI. All patients presented with symptoms of disequilibrium and/or vertigo. Charts were reviewed for demographics, symptoms, surgical procedures, videonystagmography, and degree of malformation based radiographic measurements. Results: The prevalence of Chiari Type I malformation in patients presenting to the neurotology clinic with dizziness is 16 out of 6427 (0.2%). During this time period, 16 patients were found to have radiographically confirmed Chiari Type I malformations. The mean herniation was 6.3 mm with a range of 5 to 13mm. Videonystagmography testing was done on 12 out of 16 patients and 7 out of 12 were abnormal with a mean RVR of 38%. Two of 16 patients (12.5%) underwent posterior fossa decompression. Surgical patients tended to have more severe symptoms. Conclusions: A small subset of patients who present to neurotology clinics with vertigo and/or disequilibrium will have radiographic findings of Chiari Type I malformation without the traditional symptoms of headaches and neurologic disturbances. The dilemma for clinicians is to determine if the radiographic findings are contributing to the patients symptoms or are an incidental finding. Intervention should only be considered if the herniation is greater than 10 mm, a cervical syrinx is present, or patients have the classic Chiari‐type symptoms.